Effects of exercise-induced fatigue on lower extremity joint mechanics, stiffness, and energy absorption during landings - Zhang, X.; Xia, R.; Dai, B.; Sun, X.; Fu, W. (Journal of Sports Science & Medicine, 2018)
The aim of this study was to determine the effects of two fatigue protocols on lower-limb joint mechanics, stiffness and energy absorption during drop landings. Fifteen male athletes completed landing tasks before and after two fatigue protocols (constant speed running [R-FP] and repeated shuttle sprint plus vertical jump [SJ-FP]). Sagittal plane lower-limb kinematics and ground reaction forces were recorded. Compared with R-FP, SJ-FP required significantly less intervention time to produce a fatigue state. The ranges of motion (RoM) of the hip were significantly greater when the athletes were fatigued for both protocols. Knee RoM significantly increased after SJ-FP but not after R-FP (p > 0.05), whereas the RoM of the ankle was significantly greater after R-FP but lower after SJ-FP. When fatigued, the first peak knee extension moment was significantly greater in R-FP but lower in SJ-FP; the second peak ankle plantar flexion moment was lower, regardless of protocols. After fatigue, vertical, hip, and knee stiffness was lower, and more energy was absorbed at the hip and knee for both protocols. Hip and knee extensors played a crucial role in altering movement control strategies to maintain similar impact forces and to dissipate more energy through a flexed landing posture when fatigued compared to when non-fatigued. Furthermore, SJ-FP seems to be a more efficient method to induce fatigue due to less intervention time than R-FP.